A methodology for analyzing alternative reservoir shortage and operating criteria - Oamek, George, author; Schluntz, Larry, author; Bottorft, Loren, author; Johns, Eldon, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
The Bureau of Reclamation's shifting emphasis from a construction oriented agency to a water management agency has initiated the development of analytical tools for estimating the benefits, and changes in benefits, of alternative reservoir sizes (for new projects) and operating criteria (for existing projects). This paper presents a new methodological approach for estimating the marginal, or change in, economic benefits for a project and applies it to several case studies. The modeling system developed from this effort links a spreadsheet-based model of reservoir operations to economic models of various demand sectors, including irrigation, municipal and industrial uses (M&I), and instream flow. Linking the models results in quick response in estimating the annual marginal economic benefits of alternative reservoir sizes and operating criteria. When applied to a case study of an existing Southern California reservoir, the modeling system estimated the annual benefits of reservoir enlargement and changes in operating criteria. Additional case studies for projects in Oregon, Kansas, and Colorado have demonstrated the ability of the methodology to be adapted to a wide range of hydrologic conditions and project purposes.
USCID regional meetings -- 1989
Reservoir operating criteria
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.